2007
DOI: 10.1177/0044118x07310134
|View full text |Cite
|
Sign up to set email alerts
|

School Bullying Among Hong Kong Chinese Primary Schoolchildren

Abstract: The first comprehensive survey of 7,025 Chinese primary schoolchildren found that 24% of respondents reported that they had sometimes physically bullied another child. When children observed school bullying, 56% said they immediately reported it to their teachers. Another 20% tried to stop the bullying by approaching the bullies. The study also identified factors associated with bullying. These included coming from an adverse psychosocial background and having more contact with violent values through associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 34 publications
2
52
2
Order By: Relevance
“…In Hong Kong, the prevalence rate of self-reported school bullying victimization ranged from 20% to 62% (Wong, 2004;Wong, Lok, Lo, & Ma, 2008); while bullying perpetration at school was found to range between 19% and 56% for different types of peer victimization (Ng & Tsang, 2008;Wong, Cheng, Ngan, & Ma, 2011;Wong et al, 2008a). Among others, verbal bullying was reported to be the most prevalent type of bullying behaviors in Ng and Tsang's (2008) sample of 366 secondary school students.…”
Section: Hong Kongmentioning
confidence: 99%
“…In Hong Kong, the prevalence rate of self-reported school bullying victimization ranged from 20% to 62% (Wong, 2004;Wong, Lok, Lo, & Ma, 2008); while bullying perpetration at school was found to range between 19% and 56% for different types of peer victimization (Ng & Tsang, 2008;Wong, Cheng, Ngan, & Ma, 2011;Wong et al, 2008a). Among others, verbal bullying was reported to be the most prevalent type of bullying behaviors in Ng and Tsang's (2008) sample of 366 secondary school students.…”
Section: Hong Kongmentioning
confidence: 99%
“…This finding may reflect the lesser prevalence of student misconduct and school violence in Chinese societies in the East than in societies in the West (Greenberger et al 2000;Stewart et al 1998;Wong et al 2008).…”
Section: Different Influences Of Contextual Factors On Readers With Hmentioning
confidence: 90%
“…In some schools, support from the management has led to a reduction in bullying. Chinese people are usually concerned with shame and humiliation, and shaming includes a lot of disapproving behaviors that comprise stigmatization (Wong, Lok, Lo and Ma, 2008).…”
Section: Cyber Bullyingmentioning
confidence: 99%
“…Disrespect is considered to be a minor offence. Research by Wong, Lok, Lo and Ma (2008) has shown that among respondents in the 10-14 years age group, 88% find physical bullying unacceptable, 66% find social exclusion unacceptable, while only 46% find verbal bullying unacceptable. Usually child disrespect is a part of verbal bullying, and sometimes it is evoked for the purpose of social exclusion.…”
Section: Introductionmentioning
confidence: 99%